2013
DOI: 10.3109/02688697.2013.798858
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of perioperative accidental durotomy: does the period of postoperative bed rest reduce the incidence of complication?

Abstract: A longer period of mandatory bed rest does not decrease the rate of complications. Patients should be mobilised as soon as they can. This could potentially reduce the length of hospital stay and the cost of aftercare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 13 publications
2
18
1
Order By: Relevance
“…In a retrospective analysis, Low et al 16 contended that there was no statistical signifi cance between the day of mobilization and the complication rate (low-pressure headaches, pseudomeningocele, and cerebrospinal fl uid leak) for patients with an incidental durotomy after lumbar spine surgery. In a retrospective analysis, Low et al 16 contended that there was no statistical signifi cance between the day of mobilization and the complication rate (low-pressure headaches, pseudomeningocele, and cerebrospinal fl uid leak) for patients with an incidental durotomy after lumbar spine surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective analysis, Low et al 16 contended that there was no statistical signifi cance between the day of mobilization and the complication rate (low-pressure headaches, pseudomeningocele, and cerebrospinal fl uid leak) for patients with an incidental durotomy after lumbar spine surgery. In a retrospective analysis, Low et al 16 contended that there was no statistical signifi cance between the day of mobilization and the complication rate (low-pressure headaches, pseudomeningocele, and cerebrospinal fl uid leak) for patients with an incidental durotomy after lumbar spine surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Special consideration is required before performing a lumbar decompression at an ambulatory surgery center for a patient who is at high risk for a dural tear. Recent literature has suggested that there may not be a benefit to flat bed rest for more than twenty-four hours 52,53 . However, in clinical practice, many surgeons are still managing patients with flat bed rest for twenty-four hours or more, and such treatment may not be possible at an ambulatory surgery center.…”
Section: Lumbar Spine Surgery At An Ambulatory Surgery Centermentioning
confidence: 99%
“…2,4,7,8,28 However, there is no consistency between surgeons on indication, duration, and position of the bed rest for prevention and management of CSF complications following lumbosacral spinal surgeries. 9,12,16,26,29,31 Experimental models of the dural reparative process showed that primary fibroblastic bridging of the durotomy appears at postoperative Day 6, and closure of the defect occurs at Day 10.…”
Section: Bed Restmentioning
confidence: 99%